The Stroke RiskometerTM App: The Greek Version. Live Poster Presentation - Phylactou, Phivos; Charalambous, Marina (My University, 2021)
Background1,2,3 • The Stroke RiskometerTM App was designed as a population wide prevention strategy. • Freely available mobile device application for monitoring, assessing, and modifying factors that increase stroke risk. • Predicts the approximate stroke risk of users and identifies high risk individuals. • Validated and performs similarly or better than established stroke risk factor measuring tools.
Keywords: Stroke Riskometer